Molecular dissection of ALS‐linked TDP‐43 – involvement of the Gly‐rich domain in interaction with G‐quadruplex mRNA - Ishiguro, Akira; Kimura, Nobuyuki; Noma, Takashi; Shimo‐Kon, Rieko; Ishihama, Akira; Kon, Takahide (FEBS letters, 2020)
TDP‐43 is the major pathogenic protein of amyotrophic lateral sclerosis (ALS). Previously, we identified that TDP‐43 interacts with G‐quadruplex (G4)‐containing RNA and is involved in their long‐distance transport in neurons. For the molecular dissection of the TDP‐43 and G4‐RNA interaction, we analyzed it here in vitro and in cultured cells using a set of 10 mutant TDP‐43 proteins from familial and sporadic ALS patients as well as using the TDP‐43 C‐terminal Gly‐rich domain alone. Our results altogether indicate the involvement of the Gly‐rich region of TDP‐43 in the initial recognition and binding of G4‐RNA, which then induces tight binding of TDP‐43 with target RNAs, supposedly in conjunction with its RNA recognition motifs.